DNA‐Scaffolded Multivalent Ligands to Modulate Cell Function. Issue 9 (6th May 2014) - Zhang, Zhiqing; Eckert, Mark A.; Ali, M. Monsur; Liu, Linan; Kang, Dong‐Ku; Chang, Elizabeth; Pone, Egest J.; Sender, Leonard S.; Fruman, David A.; Zhao, Weian
Abstract We report a simple, versatile, multivalent ligand system that is capable of specifically and efficiently modulating cell‐surface receptor clustering and function. The multivalent ligand is made of a polymeric DNA scaffold decorated with biorecognition ligands (i.e., antibodies) to interrogate and modulate cell receptor signaling and function. Using CD20 clustering‐mediated apoptosis in B‐cell cancer cells as a model system, we demonstrated that our multivalent ligand is significantly more effective at inducing apoptosis of target cancer cells than its monovalent counterpart. This multivalent DNA material approach represents a new chemical biology tool to interrogate cell receptor signaling and functions and to potentially manipulate such functions for the development of therapeutics.